ACT NOW: a practical toolkit for amputation reduction. Issue 5 (2nd May 2022) - Robbie, Jayne; Edmonds, Mike; Phillips, Anne; Odiase, Charles; Beckwith, Anita; Diggle, Jane; Holmes, Patrick; Grummitt, John; Walker, Kate
Abstract : Foot problems are often associated with multiple limb-threatening comorbidities for people with diabetes. It has been suggested that many of these amputations could be avoided if foot ulcers are effectively detected, assessed, referred and rapidly treated in order to optimise healing. All healthcare professionals in both primary and secondary care can have a pivotal role to play to reduce major amputations by 50%. Adopting ACT NOW and using this tool routinely can reduce the unacceptably high volume of major amputations.